PENGARUH LITERASI KEUANGAN DIGITAL DAN E-LIFESTYLE TERHADAP PERILAKU KONSUMTIF PENGGUNA E-MONEY DENGAN KONTROL DIRI SEBAGAI VARIABEL MEDIASI PADA GENERASI Z DI KOTA PALANGKA RAYA - Amellia Amellia; Eri Triani; Hafidza Umul Rizky (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study aims to analyze the influence of digital financial literacy and e-lifestyle on the consumptive behavior of e-money users among Generation Z in Palangka Raya City, with self-control as a mediating variable. This phenomenon is relevant considering the dominance of Generation Z in the city's demographic structure and the rapid adoption of digital payments, which have the potential to encourage consumptive behavior. The study employed a quantitative approach using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). Primary data were collected through questionnaires from 163 Generation Z respondents in Palangka Raya who had used e-money for at least one month. The sampling technique used was non-probability sampling (snowball sampling). The results of the study show that digital financial literacy has a negative and significant effect on consumptive behavior. In contrast, e-lifestyle has a positive and significant effect on consumptive behavior. Both independent variables also have a positive and significant effect on self-control. Self-control itself has a positive and significant effect on consumptive behavior and has been proven to act as a significant mediator in the relationship between digital financial literacy and consumptive behavior, as well as between e-lifestyle and consumptive behavior. Practically, these findings serve as recommendations for stakeholders to strengthen digital financial literacy programs and the development of self-control among Generation Z so that they can utilize the convenience of e-money wisely.